Topography of the medullar cone apex in sloths - Amorim, Marleyne José Afonso Accioly Lins; Albuquerque, Priscilla Virgínio de; Amorim Júnior, Adelmar Afonso de; Melo, Diogo D’Paula Cunha Brasileiro de; Galvão, André Puckey de Oliveira; Magalhães, Carolina Peixoto; Freitas, Manuela Figueiroa Lyra de (Revista Nordestina de Zoologia, 2014)
The sloths have arboreal animal habits and low metabolism; they belong to the order Pilosa, like anteaters. They inhabit tropical forests from Central America to northern Argentina. They are divided into two families, Bradypodidae and Megalonychidae. Their cervical vertebrae vary from six to nine, depending on species, while the lumbar joints have additional feature, known as "xenarthrales". Knowledge about the relationships between the skeleton and nervous system of sloths is relevant for comparison with other wild and domestic species and employment of anesthesia. For this study to determine topography cone sloths we used two males of the species Choloepus hoffmanni, four males and two females of the species Bradypus variegatus, all obtained after natural death. These animals were embalmed for dissection and visualization of the lumbosacral region. With the aid of a magnifying glass we observed the following topographies: in five of the six B. variegatus the termination of the cone was between the fourth lumbar and the first sacral vertebra, and in one between the third and fourth lumbar vertebra, which also was analyzed in both C. hoffmanni. It follows, that there are anatomical differences between individuals of the same or different species, and that topography of the apex of the cone found in the sloths studied was similar to that of carnivores, such as the giant otter and primates like marmosets.